Alocação ótima de chaves de interconexão nas redes de distribuição de energia elétrica - López Amézquita, Juan Camilo [UNESP] (2015)
The optimal switch allocation problem in electrical distribution systems is a combinatorial optimization problem, subject to a set of technical and operational constraints that produces complex, nonlinear, nondeterministic and, in many cases, non-analytical and difficult to represent optimization models. Therefore, the best approach to provide high quality solutions, in reasonable time, is the use of modern heuristics algorithms. This work presents an optimization methodology based on the formulation of convex mathematical models and solved by using a simplified GRASP algorithm, in order to provide high quality solutions to the switch allocation problem. The allocated switches establish an efficient restoration scheme that, in case of a permanent fault, isolates the faulty zone and restores the electrical service of as many users as possible. On the other hand, the switches allocated by the proposed methodology, are also used to optimize the steady-state operating point of the system and the reliability indices experienced by the users, i.e., the active power losses are reduced and the reliability indices, SAIDI and SAIFI, are improved when the system is operating flawlessly. In order to show the efficiency and flexibility of the proposed switch allocation methodology, two test systems have been proposed and different allocation instances have been solved